Artificial Intelligence and the Transformation of Media: Rethinking Journalism and Communication in the Algorithmic Age - Najar, Ph. D, Mehrajudin Aslam (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2025)
Artificial Intelligence (AI) has become a defining technological and cultural force in the media and communication landscape. Its integration into news production, content curation, and audience analytics has reconfigured journalistic practices, redefined professional ethics, and reshaped public discourse. Through automation, personalization, and verification systems, AI technologies now influence both how media is created and how it is understood. This conceptual paper examines AI’s multifaceted role in the transformation of media through three theoretical lenses: media ecology, technological determinism, and critical algorithm studies. It develops an analytical model, the Automation–Personalization–Verification (APV) Framework, to explain the systemic influence of AI on production, distribution, and credibility processes within journalism and digital communication. The paper argues that while AI enhances efficiency and creativity, it simultaneously generates new ethical and epistemological dilemmas concerning transparency, bias, and trust. It concludes by emphasizing the need for human-centered AI that balances technological innovation with journalistic integrity and public accountability.